A quantitative model for technology assessment - Ortigas, Glenn M.; Sharif, M. N.; Techapun Raengkhum; Tang, John C.S.; Government of the United States of America (Bangkok : Asian Institute of Technology, 1978)
A quantitative model has been developed for evaluating competing technologies which perform similar functions for an industrial project. The over-all objective of this study is to show that a project evaluation model can be used t o assess technologies in a broad socio-economic context , taking into consideration economic, social, environmental and institutional impacts to a less developed society. With such objective in mind, a total criteria set for evaluation has been identified. Evaluation factors that are relevant to these criteria has been delineated, analyzed and classified into dominant, objective and subjective factors. Using a national preference, which is a linear function of the objective and subjective factors, the general model has been formulated. Investment criteria are used to measure the utility of each technology to the economic criteria. For subjective factor quantification, two methodologies has been studied for relevance, utility and time-efficiency. The model is then applied to a beverage-can project, where two competing technologies are being considered. Sensitivity analysis has been conducted to determine the effects of parametric changes on the model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Technology assessment -- Mathematical models